2015
DOI: 10.1248/bpb.b14-00599
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Postoperative Fatigue Syndrome in Rat Model by Ginsenoside Rb1 <i>via</i> Down-Regulation of Inflammation along the NMDA Receptor Pathway in the Hippocampus

Abstract: Postoperative fatigue syndrome (POFS) is a common complication which decelerates recovery after surgery. The present study investigated the anti-fatigue effect of ginsenoside Rb1 (GRb1) through the inflammatory cytokine-mediated N-methyl-D-aspartate (NMDA) receptor pathway. A POFS rat model was created by major small intestinal resection and assessed with an open field test. Real-time quantitative polymerase chain reaction, western blot analysis, high performance liquid chromatography and a transmission electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…In our study, we have shown that there were significant elevations in the inflammatory cytokines which is pivotal to the activation of IDO-1 which subsequently reduced the level of 5-HT in the hippocampus. Our observation is in agreement with the previous reports demonstrating the activation of IDO-1 accompanied by the reduction in the 5-HT content in response to immune activation in the hippocampus of rat [49, 50]. Therefore, it should be IDO-1 instead of TDO-2 mediating the tryptophan breakdown in the hippocampus.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, we have shown that there were significant elevations in the inflammatory cytokines which is pivotal to the activation of IDO-1 which subsequently reduced the level of 5-HT in the hippocampus. Our observation is in agreement with the previous reports demonstrating the activation of IDO-1 accompanied by the reduction in the 5-HT content in response to immune activation in the hippocampus of rat [49, 50]. Therefore, it should be IDO-1 instead of TDO-2 mediating the tryptophan breakdown in the hippocampus.…”
Section: Discussionsupporting
confidence: 93%
“…Locomotor activity was composed by horizontal activity and vertical activity. It has been reported that physical fatigue could decrease locomotor activity [ 58 ], unfortunately, few literature reported the changes in locomotor activity during central fatigue. The measures of horizontal activity in this study composing total distance travelled, number of crossing squares, maximum distance travelled, and the mean velocity, it is showed a significant increase in CSD rats, and a decreasing trend after inhalation treatment without statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Peng et al [23] reported that ginsenoside Rb3 inhibited NMDA-evoked peak current in hippocampal neurons, and Ca 2+ -induced desensitization of NMDA current was facilitated. Ginsenoside Rb1 had an anti-fatigue effect on postoperative fatigue syndrome by inhibiting the expression of inflammatory cytokines and NMDA receptors [24]. It is suggested that the effects of ginsenosides Rb3 and Rb1 are partly mediated by the inactivation of the NMDA receptor.…”
Section: Discussionmentioning
confidence: 99%